Moment Risk Premia and Stock Return Predictability - Fan, Zhenzhen; Xiao, Xiao; Zhou, Hao (Journal of Financial and Quantitative Analysis, 2022)
Abstract We study the predictive power of option-implied moment risk premia embedded in the conventional variance risk premium. We find that although the second-moment risk premium predicts market returns in short horizons with positive coefficients, the third-moment (fourth-moment) risk premium predicts market returns in medium horizons with negative (positive) coefficients. Combining the higher-moment risk premia with the second-moment risk premium improves the stock return predictability over multiple horizons, both in sample and out of sample. The finding is economically significant in an asset-allocation exercise and survives a series of robustness checks.